Strengthening Marine Logistics Regulations to Support Maritime Economic Development - Misliah Misliah (Collaborate, 2024)
The maritime industry is a crucial driver of global economic growth, facilitating international trade and transportation. However, outdated and fragmented regulations governing marine logistics operations often hinder the sector's efficiency and competitiveness. This paper examines the importance of strengthening marine logistics regulations to support maritime economic development. It highlights the need for regulatory harmonization, promoting sustainability, adopting digital technologies, and fostering stakeholder collaboration. By addressing these key areas, nations can create an enabling environment for efficient and competitive marine logistics operations, unlocking new opportunities for economic growth and trade facilitation. The findings underscore the significance of regulatory reforms in enhancing the maritime industry's contribution to sustainable development and global competitiveness.